Frequency-Domain Equalization in Single-Carrier Transmission: Filter Bank Approach. (10th January 2007) - Yang Yang, Yuan Yuan; Ihalainen Ihalainen, Tero Tero; Rinne Rinne, Mika Mika; Renfors Renfors, Markku Markku
Abstract : This paper investigates the use of complex-modulated oversampled filter banks (FBs) for frequency-domain equalization (FDE) in single-carrier systems. The key aspect is mildly frequency-selective subband processing instead of a simple complex gain factor per subband. Two alternative low-complexity linear equalizer structures with MSE criterion are considered for subband-wise equalization: a complex FIR filter structure and a cascade of a linear-phase FIR filter and an allpass filter. The simulation results indicate that in a broadband wireless channel the performance of the studied FB-FDE structures, with modest number of subbands, reaches or exceeds the performance of the widely used FFT-FDE system with cyclic prefix. Furthermore, FB-FDE can perform a significant part of the baseband channel selection filtering. It is thus observed that fractionally spaced processing provides significant performance benefit, with a similar complexity to the symbol-rate system, when the baseband filtering is included. In addition, FB-FDE effectively suppresses narrowband interference present in the signal band.